Price to Book Value Drives Stock Prices in Indonesia, While DER and PER Falter - Siska Widiyawati; Sarwendah Biduri (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of the Debt to Equity Ratio (DER), Price to Book Value (PBV), and Price Earning Ratio (PER) on stock prices of food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2018. Using secondary data from financial reports and statistical analysis via SPSS 23, the research found that DER does not significantly affect stock prices, PBV positively influences stock prices, and PER has no significant impact. These findings suggest that investors prioritize market confidence and financial prospects (as indicated by PBV) over debt levels and earnings ratios when making investment decisions in this sector. Highlights: 1. DER Impact: Debt to Equity Ratio does not affect stock prices significantly.2. PBV Significance: Price to Book Value positively influences stock prices.3. PER Irrelevance: Price Earning Ratio does not impact stock prices significantly. Keywords: Debt to Equity Ratio, Price to Book Value, Price Earning Ratio, Stock Prices, Indonesia Stock Exchange